IMPLEMENTATION OF ADVERTISING AND PERSONAL SELLING TO INCREASE ROOM OCCUPANCY AT THE TRANS RESORT BALI - Ida Ayu Putu Jeni Cahyani; Budi Susanto; I Putu Astawa (Journal of Applied Sciences in Travel and Hospitality, 2018)
This research has been done to observe the implementation of advertising and personal selling at The Trans Resort Bali and the effect to increase room occupancy. Independent variables used in this research are advertising (X1) and personal selling (X2), while the dependent variable is the room occupancy (Y). The data which is used in this research are the primary data and secondary data. The primary data is by conducting interview with sales and marketing staff, and the secondary data is the cost of advertising, personal selling and the room occupancy. Data collection method which is used in this research are observation, interview, and documentation. As for data analysis technique used is multiple linear regression to explain the effect of advertising and personal selling to increase room occupancy at The Trans Resort Bali, and further processed by using SPSS 17. The advertising that has been done at The Trans Resort Bali are print advertising through flyer, newspaper and printed magazine, electronic advertising through TV channel, radio broadcast, and internet media, outdoor advertising through billboard, and specialty advertising through souvenirs such as pen, calendar, luggage tag, sport towel, and sales kit. The implemented personal selling activities that have been done are sales call to various travel agents, and domestic or foreign sales trip. The results of this research indicate that simultaneously and partially, both of the independent variables have a positive effect to the room occupancy. Based on the SPSS calculation in multiple determination analysis, the value of determination coefficient is 76,9%. It means the contribution of advertising (X1) dan personal selling (X2) is 76,9% to the room occupancy, while 23,1% can be influenced by the other factors not included in this research